Yangyin Qingre Huoxue Method in Traditional Chinese Medicine Ameliorates Atherosclerosis in ApoE−/− Mice Suffering from High-Fat Diet and HSP65 Aggression. (1st January 2019) - Qiu, Runze; Long, Jun; Zhou, Liyu; Ma, Yuanjing; Zhao, Lingang; Liu, Fumin; Yuan, Dongping
Abstract : Atherosclerosis (AS) is a complicated arterial disease resulting from abnormal lipid deposition and inflammatory injury, which is attributed to Yin deficiency, accumulation of heat materials, and stasis of blood flow in Traditional Chinese Medicine (TCM) theory. Thus, according to TCM theory, the method of nourishing Yin (Yangyin), clearing away heat (Qingre), and promoting blood circulation (Huoxue) is a reasonable strategy, which has achieved remarkable clinical efficacy in the treatment of AS, but the mechanisms remain to be known. In this study, we evaluated the effects of Yangyin Qingre Huoxue Prescription (YQHP) on AS in ApoE -/- mice suffering from a high-fat diet and heat shock protein (HSP65) attack. YQHP regulated levels of blood lipids and inflammation-linked cytokines as well as Th17/Treg ratio in peripheral blood. Suppressed IL-6-p-STAT3 signaling and restored IL-2-p-STAT5 signaling in the presence of YQHP may partake in the regulation of Th17 and Treg differentiation. Moreover, YQHP modulated transcriptional levels of costimulator CD80 in aortas as well corresponding to the downregulation of GM-CSF in serum and CD3 expression in CD4 + T cells, which might indicate the potential of YQHP to regulate antigen presenting cells. All these effects eventually promoted the improvement of atherosclerotic lesions. In addition, YQHP promoted less monocyte infiltration in the liver and lower levels of AST, ALT, and AKP production than simvastatin. Conclusively, lipid-regulating and anti-inflammatory functions mediated by YQHP with lower hepatotoxicity than simvastatin hindered the progression of HSP65 aggravated AS in ApoE -/- mice, indicating the effectiveness of Yangyin Qingre Huoxue Method in the treatment of AS.